Case Report: Recurrent Autoimmune Hypoglycemia Induced by Non-Hypoglycemic Medications - Qiuping Zhu; Qiuping Zhu; Hanxin Zhao; Wei Qiu; Fang Wu; Chungen Qian; Chungen Qian; Yonghong Yang; Ye Kang; Fenping Zheng; Jiaqiang Zhou (Frontiers in Immunology, 2022)
We present a case of recurrent autoimmune hypoglycemia induced by non-hypoglycemic agents. We review reported cases of autoimmune hypoglycemia related to non-hypoglycemic agents, and discuss the effects of different detection methods for insulin autoantibodies on the results obtained. We aim to provide information for clinicians and a warning for medication usage. Considering the increasing number of clopidogrel-induced AIH cases and the hypoglycemia-induced increase in the risk of cardiovascular events, we recommend that cardiovascular disease patients being treated with clopidogrel be informed of this rare side effect and that clinicians be vigilant for the possibility of autoimmune hypoglycemia in this patient population.